1996
DOI: 10.1001/archneur.1996.00550020079018
|View full text |Cite
|
Sign up to set email alerts
|

Regional Gray and White Matter Metabolite Differences in Subjects With AD, With Subcortical Ischemic Vascular Dementia, and Elderly Controls With 1H Magnetic Resonance Spectroscopic Imaging

Abstract: Our findings in subjects with AD suggest neuron loss in gray matter, axon loss in white matter, and altered Cho metabolism in posterior brain regions. Our findings in subjects with SIVD are consistent with higher levels of creatine-containing metabolites and/or lower levels of NAA in frontal white matter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
1
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(51 citation statements)
references
References 34 publications
(26 reference statements)
3
44
1
3
Order By: Relevance
“…An increased choline signal, a marker for membrane integrity, has also been described in AD patients, but is not found consistently [81]. Significant NAA reductions were found in the hippocampus, posterior cingulate, and gray matter of the temporal, parietal, and sometimes the occipital and frontal lobes [82][83][84][85][86][87][88][89]. The degree of cognitive impairment was found to be well correlated with the degree of NAA decrease [90].…”
Section: Other Potential Neuroimaging Biomarkersmentioning
confidence: 93%
See 1 more Smart Citation
“…An increased choline signal, a marker for membrane integrity, has also been described in AD patients, but is not found consistently [81]. Significant NAA reductions were found in the hippocampus, posterior cingulate, and gray matter of the temporal, parietal, and sometimes the occipital and frontal lobes [82][83][84][85][86][87][88][89]. The degree of cognitive impairment was found to be well correlated with the degree of NAA decrease [90].…”
Section: Other Potential Neuroimaging Biomarkersmentioning
confidence: 93%
“…The degree of cognitive impairment was found to be well correlated with the degree of NAA decrease [90]. In addition, several studies found MRS also useful in differentiating AD from other forms of dementia, eg, vascular dementia, fronto-temporal lobe dementia [85,86,[91][92][93].…”
Section: Other Potential Neuroimaging Biomarkersmentioning
confidence: 95%
“…NAA levels are decreased in vascular dementia, even in cortical regions remote from the infarction. [34][35][36] With the additional information gained from elevated glial metabolite mI, it is possible that NAA/mI ratio on MRS has a higher sensitivity in detecting cellular and molecular changes associated with small-vessel disease than WMH load. This hypothesis needs to be tested in an autopsy-confirmed sample.…”
Section: Mrimentioning
confidence: 99%
“…1 H MRS metabolite changes in FTLD are similar to AD, with lower NAA /Cr and higher mI /Cr levels than normal (14,15). 1 H MRS studies in common dementias are limited to comparing the 1 H MRS findings in AD to other dementias (14), FTLD (15) and VaD (11)(12)(13)16). We are not aware of any study that has compared the 1 H MRS metabolite profiles among the most common dementias.…”
Section: Introductionmentioning
confidence: 99%